Nanocapsulated Ascorbic Acid in Combating Cerebral Ischemia Reperfusion- Induced Oxidative Injury in Rat Brain - Sarkar, Sibani; Mukherjee, Abhishek; Swarnakar, Snehasikta; Das, Nirmalendu (Current Alzheimer Research, 2016)
Recent evidences suggest that cerebral ischemia-reperfusion insult plays significant role in pathogenic diseases like Alzheimer’s disease (AD) and other neurodegenerative diseases. Toxic reactive oxygen species (ROS) generated by induced oxidative stress in the episodes of cerebral ischemia-reperfusion (CIR) plays major role in neurodegeneration. As the prime source of ROS generation, neuronal mitochondria, the cellular energy metabolic centre experience severe damage because of CIR-induced oxidative stress. The process of mitochondrial dysfunction is accelerated by CIR that may pave the pathway for neurodegeneration in AD among aged individuals. Prevention of CIR injury may be a shunt in order to minimize the risk of dementia of Alzheimer’s type in aged individuals. The use of chemical antioxidants in CIR is not suitable as the blood- brain barrier (BBB) doesn’t allow the entry of molecules from blood circulation into the brain. Thus L-ascorbic acid loaded polylactide nanocapsules were prepared and fed orally to assess the role of nanocapsulated ascorbic acid (NAA) against CIR induced oxidative injury in mitochondrial region of rat brains. Mitochondrial injury was assessed by the extent of lipid peroxidation and in situ antioxidant enzyme status. The levels of cytochrome c (cyt c), cyclooxygenase- 2 (COX-2) and iNOS were determined. Results showed that in comparison to free ascorbic acid (AA), NAA exerted better protection to the brain mitochondria by preventing oxidative damage in ROS mediated CIR injury.
Keywords: oxidative stress